Peningkatan Hasil Belajar Matematika Melalui Pendekatan Kontekstual Konsep Bangun Ruang Menggunakan Video Compact Disc - Siti Rohani Ipa; Djaffar Lessy; Rizal Kamsurya; Lastri Lastri (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Video media has considerable potential if used as a learning medium that allows students to directly observe the real form of objects. This study aims to determine the improvement of mathematics learning outcomes through a contextual approach to the volume material of building space using a video compact disc. The type of research used is classroom action research and consists of four stages, namely planning, action, observation, and reflection and the number of subjects amounted to 30 people. The instruments used are tests and observation sheets. Tests are used to determine student learning outcomes and observation is used to determine student activities in the learning process. Data analysis techniques are used descriptively. The results of data analysis obtained that the application of contextual approaches can improve student learning outcomes. This result is intended by increasing test results in cycle I, and cycle II which is carried out with a contextual approach. If in cycle I the learning process has not taken place optimally because students are still not serious in learning and class management is still lacking by the teacher, in cycle II the learning process that takes place is in accordance with the learning steps and students can discuss with their friends in class